Welfare impact of broadening VAT by exempting local food markets: The case of Bangladesh - Jörgen Levin; Yeasmin Sayeed (Örebro University School of Business, 2014)
The spread of value-added tax (VAT) in developing countries has been dramatic since the beginning of 1990's. Adopted by more than 130 countries, including many of the poorest, VAT has been, and remains, the key of tax reform in many developing countries. While adopting VAT, there are arguments for and against uniform general VAT system. A uniform and general VAT on all commodities is considered to be efficient and less distortionary. On the other hand, from the distributional perspective many goods especially food is exempted from VAT as low income households spend a high share of income on food. The contribution of this study is to analyze the income distribution and welfare impact of VAT reform when the food sectors are divided into local markets and supermarkets. A Computable General Equilibrium (CGE) model is used to evaluate the consequences of VAT reforms for Bangladesh. Our simulation results show that, a VAT reform that exempts the agriculture sector and local market food commodities provides the best welfare and distributional impact.
Keywords: H21; H22; H23; I31; 330; VAT; VAT reform; incidence analysis; equity and welfare; CGE; Bangladesh